العوامل الاقتصادية المحددة للاستثمار الاجنبي المباشر الخارج - د. بشار احمد عبدالرزاق (PROSPECTIVE RESEARCHES, 2023)
The attempt of the economic entities to increase the amounts of their foreign investments (in order to achieve the highest incomes) has made them subject to a list of economic variables which play an important role in determining their sizes which have changed through the last twenty years (relatively spearing upwards coping with the global economic changes) these changes had negative impact on the hosting countries which include developing countries. In order to discover and determine the key economic elements, which govern direct foreign investments according to the first five countries which export investments, the researcher has depended on the theoretical bases and analytical studies which dealt with that type of investment, using the amount method which is based on estimating the equation of the algorithmic declaration of the direct foreign investment as a variable which depend on a different group of economic variables. The researcher has used data of sequences of periods from 1990 to 2006. The researcher found that the rate of economic growth and interest rates in those countries had the most important role in determining the investments. But the economic and non-economic policies updated by the countries that want to attract high level of direct foreign investment are still more important in attracting investment towards these countries.